Finite element simulation and optimization of radial resistive force for shape memory alloy vertebral body stent. (September 2017) - Wang, Rong; Zuo, Hong; Yang, Yi-Min; Yang, Bo; Li, Qun
Vertebral body stent of shape memory alloy is an innovative device which helps recover the compression fractural vertebral at normal height due to its excellent superelasticity and the shape memory effect. A finite element modeling is carried out to optimize the mechanical behavior of the vertebral body stent of shape memory alloy accounting for the stress-induced phase transformation of the shape memory alloy. The radial resistive force of stent is paid more attention in order to meet the functional and surgical requirement. First, experimental procedure and finite element modeling computations are constructed to calculate the compression resistance force of an original design of vertebral body stent of shape memory alloy. It is found that numerical results are consistent with those of experimental observations so as to validate the accuracy of the finite element modeling model. Second, a series of numerical simulations are performed to optimize the topological structures of vertebral body stent of shape memory alloy by response surface methodology. The surgical condition of the lumen structure of fracture vertebral body and the size constrain condition of puncture instrument of minimally invasive surgery are introduced during finite element modeling simulation and response surface methodology optimization. Finally, an innovative design optimization is proposed by the series–parallel connection of four S-type representative stents. The proposed new structure can obtain the maximum radial resistive force of 831 N which is able to meet the functional requirement. In conclusion, it is expected that the finite element modeling simulations and optimizations can help the researchers to design and optimize the topological structures of vertebral body stent of shape memory alloy systems.